Dramatic response to alectinib in an ALK‐positive LCNEC patient with a poor performance status: A case report. Issue 9 (3rd August 2021) - Masuda, Kazuki; Saiki, Masafumi; Shimamura, So; Ide, Shuichiro; Uchida, Yoshinori; Sogami, Yusuke; Ishihara, Hiroshi; Ikeda, Fumi; Kugiyama, Kiyotaka
Abstract: The echinoderm microtubule‐associated protein‐like 4 ( EML4 )–anaplastic lymphoma kinase ( ALK ) fusion gene, a driver mutation in lung carcinoma, is fairly common in lung adenocarcinoma but rare in large cell neuroendocrine carcinoma (LCNEC). Here we report a case of stage IV LCNEC positive for this fusion gene in a patient with a poor performance status (PS) who was effectively treated with alectinib. The patient was a 72‐year‐old non‐smoking man diagnosed as LCNEC with multiple metastases. Because of his poor PS, cytotoxic chemotherapy was not indicated, but he was later found to be positive for the ALK fusion gene and treated with alectinib as first‐line therapy. One month later, the tumour had shrunk remarkably, and the therapeutic effect was rated as a partial response. The PS also improved from 4 to 1. Investigating actionable driver mutations seems worth doing for advanced LCNEC, especially if the patient's PS is poor. Abstract : We report a patient with LCNEC harbouring ALK rearrangement with a poor performance status, who showed a good response to alectinib as first‐line treatment. The patient's PS also improved, made him eligible for further chemotherapy when alectinib had failed.